2015
DOI: 10.1088/0953-4075/48/14/144028
|View full text |Cite
|
Sign up to set email alerts
|

On the interpretation of high-resolution x-ray spectra from JET with an ITER-like wall

Abstract: The upgraded x-ray crystal spectrometer KX1 on the Joint European Torus (JET) can now measure the M x-ray lines from tungsten with sufficiently high resolution to evaluate how much tungsten may sputter from the plasma-facing tungsten wall planned for the International Thermonuclear Experimental Reactor (ITER). However, a test run on JET found that the L x-ray lines of a molybdenum impurity, which happen to occur in the targeted wavelength region of 5.00–5.35 Å, must be taken into account together with the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
0
18
1
Order By: Relevance
“…In the case of changes in plasma evolution it has been shown that with Bayesian learning and maximum of fuzzy entropy can be reached all probabilistic distributions, including non-Gibbsians distributions [24,25]. As reference papers concerning the diagnostic of high-temperature plasma conditions in tokamak reactors under the effect of plasmawall interaction see [26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of changes in plasma evolution it has been shown that with Bayesian learning and maximum of fuzzy entropy can be reached all probabilistic distributions, including non-Gibbsians distributions [24,25]. As reference papers concerning the diagnostic of high-temperature plasma conditions in tokamak reactors under the effect of plasmawall interaction see [26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Plasma diagnostics based on spectra that compensate their modest energy resolution with a large energy range and the associated modeling [1][2][3][4][5][6][7][8][9] can be just as useful as the complementary approach, taken here and in an earlier paper [10], that interprets the details in the shape of a few overlapping lines in terms of the plasma parameters. This paper shows how to determine the emission contributions from tungsten and molybdenum ions in X-ray spectra measured, in the specific wavelength region covered by the high-resolution crystal spectrometer KX1, which is local, JET specific assignment for the plasma parameters diagnostic [9][10][11][12][13][14]. As before [10], the analysis here applies to the plasmas that are test beds for ITER, notably the operating scenarios planned for JET with the ITER-like wall, and for the deuterium-tritium (DT) campaign.…”
Section: Introductionmentioning
confidence: 99%
“…This paper shows how to determine the emission contributions from tungsten and molybdenum ions in X-ray spectra measured, in the specific wavelength region covered by the high-resolution crystal spectrometer KX1, which is local, JET specific assignment for the plasma parameters diagnostic [9][10][11][12][13][14]. As before [10], the analysis here applies to the plasmas that are test beds for ITER, notably the operating scenarios planned for JET with the ITER-like wall, and for the deuterium-tritium (DT) campaign. We demonstrate that, with careful analysis, a minute spectral region already contains sufficient information to determine certain plasma parameters for a high-temperature tokamak plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate atomic data of highly-charged ions are important in both astrophysics and fusion plasmas research, such as plasma control and plasma diagnostics [1]. As a rare gas, Krypton can easily be introduced into the plasma and does not pollute the vacuum vessel.…”
Section: Introductionmentioning
confidence: 99%